Effect of clinical decision support on documented guideline adherence for head CT in emergency department patients with mild traumatic brain injury. (17th February 2014) - Gupta, Anurag; Ip, Ivan K; Raja, Ali S; Andruchow, James E; Sodickson, Aaron; Khorasani, Ramin
Abstract: Imaging utilization in emergency departments (EDs) has increased significantly. More than half of the 1.2 million patients with mild traumatic brain injury (MTBI) presenting to US EDs receive head CT. While evidence-based guidelines can help emergency clinicians decide whether to obtain head CT in these patients, adoption of these guidelines has been highly variable. Promulgation of imaging efficiency guidelines by the National Quality Forum has intensified the need for performance reporting, but measuring adherence to these imaging guidelines currently requires labor-intensive and potentially inaccurate manual chart review. We implemented clinical decision support (CDS) based on published evidence to guide emergency clinicians towards appropriate head CT use in patients with MTBI and automated data capture needed for unambiguous guideline adherence metrics. Implementation of the CDS was associated with a 56% relative increase in documented adherence to evidence-based guidelines for imaging in ED patients with MTBI.